GERAÇÃO DE INOVAÇÃO NA AGRICULTURA FAMILIAR POR MEIO DO CONHECIMENTO - Machado, Adriane de Fátima (2019)
Knowledge is the fundamental element for pursuing and achieving good results. The family farmer seeks knowledge to improve the quality of life, to acquire a competitive advantage and, in particular, to empower future consumer markets. Trainings, lectures and field days cooperate to break down barriers and provide openness to innovations and a new look at your property as a rural enterprise that can generate income and provide for the family. In this context, this study aims to understand how knowledge generates innovation for family agriculture in the municipality of Pinhão - Paraná. The methodology used to approach this study was the descriptive research, with qualitative approach and to analyze the data was carried out content analysis, divided into two guiding axes, the first knowledge and the second innovation. Afterwards, bibliographical researches were done in national and international references for the construction of the theoretical reference and to give basis for this dissertation. With the categories of analysis: knowledge in family agriculture; nature of innovations; innovation in agriculture. After this procedure, the field research was carried out by means of non-participant observation and semi structured interview with nine participants divided into three groups: family farmers with main activity of agricultural producers, dairy production and production of beef cattle. After completing the data collection, the results obtained were that all family farmers who seek knowledge through the most diverse means, achieve favorable positive results, in addition to adopting innovations and persisting in the search for learning. When analyzing the family agricultural environment, it is verified that they face struggles and difficulties so it is necessary to innovate to stay active in the market, an alternative is the formation of agroindustry in the property that represents a dream to these family farmers, so they are able to sell their products and services to other consumer markets. These farmers have a quality seal, indicating the origin of the food, with expiration date, lot and other important data to the consumer to know the origin of the product that is consuming. Another important factor is organic production as an alternative of change in the field, producing products without using chemicals, where it reaches a niche market of conscious consumers and willing to pay an extra price for the quality of the product. The main limiting factors for the development of innovation in this segment are the fear of change, marketing channels, distance from localities, public policies and the factors that facilitate innovation, increase productivity, increase financial returns, improve management and cultivation techniques. Thus, it is concluded that knowledge is a link between innovation and family farming, contributing to the entry of technology and competitive advantage.